The Meniscus midges of Costa Rica (Diptera: Dixidae) - Chaverri, Luis Guillermo; Borkent, Art (Zootaxa, 2007)
A revision of the Dixidae of Costa Rica indicates that 10 named species of Dixella are present, eight of which are described as new (described stages indicated): D. fernandezae (%), D. hansoni (%),  D. hernandezi (%), D. jironi (%), D. lobata (%, &), D. maculata (%, &), D. suzukii (%, &), D. woodi (%).  Two named species were previously known from Costa Rica: D. shannoni Lane (%, &) and D. venezuelensis Lane (%, &).  A key to the species of Costa Rica is provided and other similar Neotropical species discussed.  An overview of all Central American species is given.  Five of the 10 Costa Rican species were collected above 1200 meters in elevation, indicating that further collecting, especially at high elevations will reveal further species.  Five additional species from Costa Rica remain unnamed because they are represented only by females.  A total of 15 species of Dixella are therefore present in this country.